Tropical Forests - New Edition 2018
DOI: 10.5772/intechopen.77380
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemistry and Utilization of Wood Vinegar from Carbonization of Tropical Biomass Waste

Abstract: Pyroligneous acid also called wood vinegar is an aqueous liquid produced from pyrolysis of lignocellulose waste and biomass. In general, the pyrolysis types are classified base on heating rate mainly either fast or slow pyrolysis. The characteristic and properties of wood vinegar are primarily influenced by the type of carbonaceous feedstocks as well as the production techniques. Wood vinegar is a complex mixture of polar and non-polar chemicals with various molecular weights and compositions. Its major consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 31 publications
4
39
0
4
Order By: Relevance
“…Carbonization can be defined as a conversion of biomass precursors into a highly carbonaceous, charcoal-like material where it will be heated in an oxygen-free or oxygen-limited environment, and the reaction conditions are tailored to maximize the char production [23]. However, lower carbonization temperature (<500 C) [24] is much preferred for a high amount of char produced because slow heating will make the precursors decompose in an orderly manner. In addition, this process will form a stable molecule with richer carbon content and converging toward the hexagonal structure of graphitic carbon [25].…”
Section: Conversion Methodsmentioning
confidence: 99%
“…Carbonization can be defined as a conversion of biomass precursors into a highly carbonaceous, charcoal-like material where it will be heated in an oxygen-free or oxygen-limited environment, and the reaction conditions are tailored to maximize the char production [23]. However, lower carbonization temperature (<500 C) [24] is much preferred for a high amount of char produced because slow heating will make the precursors decompose in an orderly manner. In addition, this process will form a stable molecule with richer carbon content and converging toward the hexagonal structure of graphitic carbon [25].…”
Section: Conversion Methodsmentioning
confidence: 99%
“…7 The main proportion of PA is water (80-90%) and the rest consists of organic compounds comprising organic acids, alkane, phenolic, alcohol, and ester. 3,4 It was reported that the crude PA yield from sawdust of Chinese fir increased with an increase in pyrolysis temperature from 250 to 550 °C. 8 However, the yield of the refined wood vinegar increased until a temperature of 350 °C was reached and then decreased.…”
Section: Introductionmentioning
confidence: 99%
“…2 If the container is left for about 3 months without shaking, three phases are formed, with different weights: they include wood tar at the bottom, crude wood vinegar (also called pyroligneous acid) in the middle, and a thin layer of light oil at the top. 3 Most of the reports on the production and application of PA have been from East and Southeast Asian countries; where wood vinegar is traditionally used for a variety of purposes with a long history in farming to enhance crop and soil productivity as well as a pesticide. 2,4 Pyrolysis acid is achievable from any biomass types but it is generally obtained from the wood of broad leaf species or bamboo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El ácido piroleñoso también llamado vinagre de madera es un líquido acuoso producido a partir de la pirolisis de biomasa como sub producto de la obtención de carbón, se obtiene por la condensación del humo generados durante la pirolisis de la biomasa de 450 -600 °C, este líquido tiene un ahumado especial, el olor y el color son de amarillo claro a marrón (Theapparat, Chandumpai y Faroongsarng, 2018).…”
Section: Introductionunclassified